The Weird World of Nanotechnology - MUKHERJEE, P.K. (SCHOOL SCIENCE, 2007)
IN THE ANNUAL meeting of the Americal Physical Society, held on 29 December 1959, the Nobel Laureate physicist Richard Feynman delivered a talk entitled “There’s Plenty of Room at the Bottom”. In this talk he said, “What I want to talk about is the problem of manipulating and controlling things on a small scale ... What I have demonstrated is that there is room – that you can decrease the size of things in a practical way. I now want to show that there is plenty of room ...”. The essence of Feynman’s lecture was that there is a lot of scope for research on materials on a very small, i.e. nonometre scale. However, there may be new laws of physics governing the behaviour of matter at such (nano) scale.